Treatment of experimental periodontitis in rats using repeated adjunctive antimicrobial photodynamic therapy - Garcia, Valdir Gouveia [UNESP]; Longo, Mariéllen [UNESP]; Fernandes, Leandro Araújo [UNESP]; Gualberto Junior, Erivan Clementino [UNESP]; Santos Santinoni, Carolina dos [UNESP]; Bosco, Álvaro Francisco [UNESP]; Nagata, Maria José Hitomi [UNESP]; Theodoro, Letícia Helena [UNESP] (Springer Nature, 2013)
The aim of this study was to histologically and histometrically evaluate the influence of repeated adjunctive antimicrobial photodynamic therapy (aPDT) on bone loss (BL) in furcation areas in rats. Periodontitis was induced by placing a ligature around the mandibular molar in 75 rats. The animals were divided into five groups: the SS group was treated with saline solution (SS); the SRP group received scaling and root planing (SRP); the aPDT1 group received SRP as well as toluidine blue (TBO) and low-level laser therapy (LLLT; InGaAlP, 660 nm; 4.94 J/cm2/point) postoperatively at 0 h; the aPDT2 group received SRP as well as TBO and LLLT postoperatively at 0, 24, 28, and 72 h; and the aPDT3 group received SRP, TBO, and LLLT postoperatively at 0, 48, 96, and 144 h. The area of BL in the furcation region of the molar was histometrically analyzed. Data were analyzed statistically (P < 0.05). Animals treated with a single episode of aPDT showed less BL at days 7 and 30 than those who received only SRP treatment. No significant differences were found among the aPDT groups (P > 0.05). Repeated aPDT did not improve BL reduction when compared to a single episode of aPDT. © 2012 Springer-Verlag London Ltd.
Keywords: Alveolar bone loss; Lasers; Periodontitis; Photochemotherapy; tolonium chloride; animal experiment; animal model; animal tissue; controlled study; histology; histometry; indium gallium aluminum phosphorus laser; laser; low level laser therapy; male; molar tooth; nonhuman; osteolysis; periodontitis; photodynamic therapy; preventive dentistry; priority journal; rat; Alveolar Bone Loss; Analysis of Variance; Animals; Dental Scaling; Laser Therapy, Low-Level; Male; Rats; Rats, Wistar; Root Planing; Sodium Chloride; Tolonium Chloride